Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Benthic bacterial communities are shaped by browning in boreal headwater streams - Joanna Brüsecke; Timo Muotka; Kaisa‐Leena Huttunen; Kaisa Lehosmaa; Jussi Jyväsjärvi (Limnology and Oceanography, 2025)
Owing to the rapid progress of high‐throughput sequencing technologies, microbial assemblages have gained growing interest in environmental impact assessment. However, research on microbial community responses, particularly those of benthic biofilm, to browning (increased concentrations of dissolved organic carbon [DOC]), is scarce. We used data from 55 boreal streams to examine if biofilm bacterial communities exhibit changes in diversity and community composition along a gradient of browning (3.6–27 mg DOC L −1 ). Species richness increased slightly with increasing DOC, whereas community composition changed markedly across the gradient, especially in the active community. Pseudomonadota and Bacteroidota were overall dominant bacterial phyla. In the active community, Bacteroidota became relatively less abundant and Pseudomonadota more abundant with increasing DOC. Nitrate‐N (NO 3 ‐N) and DOC were the most important predictors of bacterial community turnover. The greatest change in community composition occurred between 75 and 100 μ g NO 3 ‐N L −1 . For DOC, the first change point was at the low‐end of the gradient, followed by a major change in strongly brownified waters (> 20 mg L −1 ). Bacterial communities became phylogenetically more similar than expected by chance as DOC increased. Concordance between bacterial and benthic invertebrate communities was very high, indicating that browning exerts a strong control over both taxonomic groups. Our results suggest that microbial communities, particularly the active portion of the community, may provide a sensitive and reliable tool for stream bioassessment. We defined a threshold‐type response in bacterial assemblages to water browning but more research is needed on microbial responses to multiple simultaneous stressors related to global warming and land‐use intensification.

Bacterial rarity in a subarctic stream network: Biodiversity patterns, assembly mechanisms and types of rarity - Jacqueline Malazarte; Timo Muotka; Jussi Jyväsjärvi; Kaisa Lehosmaa; Kaisa‐Riikka Mustonen; Laura Tarvainen; Kaisa‐Leena Huttunen (Environmental Microbiology, 2024)
Dendritic stream networks are an intriguing subject for exploring the spatial and temporal variability of the rare and common bacterial biosphere, yet very few such studies have been conducted. We sampled riverine bacterioplankton at 13 sites in a subarctic riverine network across 3 years, with five sampling times each year. Ordinations showed a consistent pattern of downstream shift for both rare and abundant subcommunities. We also detected a temporal signal, with seasonal community shifts reflecting changes in water temperature and groundwater contribution, and an inter‐annual pattern where the year 2018 differed from other years. Phylogenetic turnover of the rare subcommunity indicated homogeneous selection, whereas the abundant subcommunity was mainly stochastically structured. Transiently rare taxa were the dominant type of rarity with the highest proportion at the headwater regions. The bacterioplankton community was characterized by a small group of core taxa that occurred at most sites with little temporal variation, a very large number of permanently or transiently rare taxa, and taxa shifting through time between the rare and abundant biosphere. While this basic structure could have been detected with less extensive temporal replication, a comprehensive understanding of the rare biosphere in riverine bacterioplankton can only be achieved via inter‐annual, spatially replicated sampling that covers the whole stream network.

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Downstream impacts of peatland drainage on headwater stream biodiversity and ecosystem functioning - Iina Koivunen; Timo Muotka; Mika Jokikokko; Risto Virtanen; Jussi Jyväsjärvi (Forest Ecology and Management, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Bacterial communities in a subarctic stream network: Spatial and seasonal patterns of benthic biofilm and bacterioplankton - Jacqueline Malazarte; Timo Muotka; Jussi Jyväsjärvi; Kaisa Lehosmaa; Joel Nyberg; Kaisa‐Leena Huttunen (Molecular Ecology, 2022)
Water‐column bacterial communities are assembled by different mechanisms at different stream network positions, with headwater communities being controlled by mass effects (advection of bacteria from terrestrial soils) while downstream communities are mainly driven by environmental sorting. Conversely, benthic biofilms are colonized largely by the same set of taxa across the entire network. However, direct comparisons of biofilm and bacterioplankton communities along whole stream networks are rare. We used 16S rRNA gene amplicon sequencing to explore the spatiotemporal variability of benthic biofilm (2 weeks old vs. mature biofilm) and water‐column communities at different network positions of a subarctic stream from early summer to late autumn. Amplicon sequence variant (ASV) richness of mature biofilm was about 2.5 times higher than that of early biofilm, yet the pattern of seasonality was the same, with the highest richness in midsummer. Biofilm bacterial richness was unrelated to network position whereas bacterioplankton diversity was negatively related to water residence time and distance from the source. This pattern of decreasing diversity along the network was strongest around midsummer and diminished greatly as water level increased towards autumn. Biofilm communities were phylogenetically clustered at all network positions while bacterioplankton assemblages were phylogenetically clustered only at the most downstream site. Both early and mature biofilm communities already differed significantly between upstream (1st order) and midstream (2nd order) sections. Network position was also related to variation in bacterioplankton communities, with upstream sites harbouring substantially more unique taxa (44% of all upstream taxa) than midstream (20%) or downstream (8%) sites. Some of the taxa that were dominant in downstream sections were already present in the upmost headwaters, and even in riparian soils, where they were very rare (relative abundance

Dark matters: Contrasting responses of stream biofilm to browning and loss of riparian shading - Jussi Jyväsjärvi; Maria Rajakallio; Joanna Brüsecke; Kaisa‐Leena Huttunen; Ari Huusko; Timo Muotka; Sami J. Taipale (Global Change Biology, 2022)
Concentrations of terrestrial‐derived dissolved organic carbon (DOC) in freshwater ecosystems have increased consistently, causing freshwater browning. The mechanisms behind browning are complex, but in forestry‐intensive regions browning is accelerated by land drainage. Forestry actions in streamside riparian forests alter canopy shading, which together with browning is expected to exert a complex and largely unpredictable control over key ecosystem functions. We conducted a stream mesocosm experiment with three levels of browning (ambient vs. moderate vs. high, with 2.7 and 5.5‐fold increase, respectively, in absorbance) crossed with two levels of riparian shading (70% light reduction vs. open canopy) to explore the individual and combined effects of browning and loss of shading on the quantity (algal biomass) and nutritional quality (polyunsaturated fatty acid and sterol content) of the periphytic biofilm. We also conducted a field survey of differently colored (4.7 to 26.2 mg DOC L −1 ) streams to provide a ‘reality check’ for our experimental findings. Browning reduced greatly the algal biomass, suppressed the availability of essential polyunsaturated fatty acids, especially eicosapentaenoic acid (EPA), and sterols, but increased the availability of terrestrial‐derived long‐chain saturated fatty acids (LSAFA). In contrast, loss of shading increased primary productivity, which resulted in elevated sterol and EPA contents of the biofilm. The field survey largely repeated the same pattern: biofilm nutritional quality decreased significantly with increasing DOC, as indicated particularly by a decrease of the ω ‐3: ω ‐6 ratio and increase in LSAFA content. Algal biomass, in contrast, was mainly controlled by dissolved inorganic nitrogen (DIN) concentration, while DOC concentration was of minor importance. The ongoing browning process is inducing a dramatic reduction in the nutritional quality of the stream biofilm. Such degradation of the major high‐quality food source available for stream consumers may reduce the trophic transfer efficiency in stream ecosystems, potentially extending across the stream‐forest ecotone.

Bacterial communities at a groundwater‐surface water ecotone: gradual change or abrupt transition points along a contamination gradient? - Kaisa Lehosmaa; Timo Muotka; Anna Maria Pirttilä; Iikka Jaakola; Pekka M. Rossi; Jussi Jyväsjärvi (Environmental Microbiology, 2021)
Summary Microbial communities contribute greatly to groundwater quality, but the impacts of land‐use practices on bacteria in groundwaters and groundwater‐dependent ecosystems remain poorly known. With 16S rRNA gene amplicon sequencing, we assessed bacterial community composition at the groundwater‐surface water ecotone of boreal springs impacted by urbanization and agriculture, using spring water nitrate‐N as a surrogate of contamination. We also measured the rate of a key ecosystem process, organic matter decomposition. We documented a recurrent pattern across all major bacterial phyla where diversity started to decrease at unexpectedly low nitrate‐N concentrations (100–300 μg L −1 ). At 400 NO 3 − ‐N μg L −1 , 25 bacterial exact sequence variants showed a negative response, resulting in a distinct threshold in bacterial community composition. Chthonomonas , Acetobacterales and Hyphomicrobium were the most sensitive taxa, while only three taxa ( Duganella , Undibacterium and Thermoanaerobaculaceae ) were enriched due to increased contamination. Decomposition rate responded unimodally to increasing nitrate‐N concentration, with a peak rate at ~400 NO 3 − ‐N μg L −1 , parallelly with a major shift in bacterial community composition. Our results emphasize the utility of bacterial communities in the assessment of groundwater‐dependent ecosystems. They also call for a careful reconsideration of threshold nitrate values for defining groundwater ecosystem health and protecting their microbial biodiversity.

Habitat patchiness, ecological connectivity and the uneven recovery of boreal stream ecosystems from an experimental drought - Amélie Truchy; Romain Sarremejane; Timo Muotka; Heikki Mykrä; David G. Angeler; Kaisa Lehosmaa; Ari Huusko; Richard K. Johnson; Ryan A. Sponseller; Brendan G. McKie (Global Change Biology, 2020)
Ongoing climate change is increasing the occurrence and intensity of drought episodes worldwide, including in boreal regions not previously regarded as drought prone, and where the impacts of drought remain poorly understood. Ecological connectivity is one factor that might influence community structure and ecosystem functioning post‐drought, by facilitating the recovery of sensitive species via dispersal at both local (e.g. a nearby habitat patch) and regional (from other systems within the same region) scales. In an outdoor mesocosm experiment, we investigated how impacts of drought on boreal stream ecosystems are altered by the spatial arrangement of local habitat patches within stream channels, and variation in ecological connectivity with a regional species pool. We measured basal ecosystem processes underlying carbon and nutrient cycling: (a) algal biomass accrual; (b) microbial respiration; and (c) decomposition of organic matter, and sampled communities of aquatic fungi and benthic invertebrates. An 8‐day drought event had strong impacts on both community structure and ecosystem functioning, including algal accrual, leaf decomposition and microbial respiration, with many of these impacts persisting even after water levels had been restored for 3.5 weeks. Enhanced connectivity with the regional species pool and increased aggregation of habitat patches also affected multiple response variables, especially those associated with microbes, and in some cases reduced the effects of drought to a small extent. This indicates that spatial processes might play a role in the resilience of communities and ecosystem functioning, given enough time. These effects were however insufficient to facilitate significant recovery in algal growth before seasonal dieback began in autumn. The limited resilience of ecosystem functioning in our experiment suggests that even short‐term droughts can have extended consequences for stream ecosystems in the world's vast boreal region, and especially on the ecosystem processes and services mediated by algal biofilms.

Aquatic bryophytes play a key role in sediment-stressed boreal headwater streams - Jarno Turunen; Timo Muotka; Jukka Aroviita (Hydrobiologia, 2020)
Forestry-related land use can cause increasing instream sedimentation, burying and eradicating stream bryophytes, with severe ecological consequences. However, there is limited understanding of the relative roles and overall importance of the two frequently co-occurring stressors, increased fine sediments and loss of bryophytes, to stream biodiversity and ecosystem functions. By using random forest modeling and partial dependence functions, we studied the relative importance of stream bryophytes and fine sediments to multiple biological endpoints (leaf-decaying fungi, diatom, bryophyte, and benthic macroinvertebrate communities; leaf decomposition) using field survey data from headwater streams. Stream bryophyte abundance and richness were negatively related to fine sediment cover, highlighting the detrimental effect of sedimentation on bryophytes. However, bryophyte abundance was consistently more important a determinant of variation in community composition than was fine sediment cover. Leaf decomposition was influenced by shredder abundance, water temperature and, to a lesser degree, stream size. Our results suggest that the loss of stream bryophytes due to increasing sedimentation, rather than fine sediments per se, seems to be the key factor affecting multiple biological responses. Enhancing the re-establishment of bryophyte stands could partly compensate for the negative impacts of sedimentation on bryophytes and, consequently, on several other components of boreal stream ecosystems.

Synthesis of habitat restoration impacts on young-of-the-year salmonids in boreal rivers - Maare Marttila; Pauliina Louhi; Ari Huusko; Teppo Vehanen; Aki Mäki-Petäys; Jaakko Erkinaro; Jukka Tapani Syrjänen; Timo Muotka (Reviews in Fish Biology and Fisheries, 2019)

Local geology determines responses of stream producers and fungal decomposers to nutrient enrichment: A field experiment - Heikki Mykrä; Romain Sarremejane; Tiina Laamanen; Satu Maaria Karjalainen; Annamari Markkola; Sirkku Lehtinen; Kaisa Lehosmaa; Timo Muotka (Ambio, 2019)

Identifying taxonomic and functional surrogates for spring biodiversity conservation - Jussi Jyväsjärvi; Risto Virtanen; Jari Ilmonen; Lauri Paasivirta; Timo Muotka (Conservation Biology, 2018)
Surrogate approaches are widely used to estimate overall taxonomic diversity for conservation planning. Surrogate taxa are frequently selected based on rarity or charisma, whereas selection through statistical modeling has been applied rarely. We used boosted‐regression‐tree models (BRT) fitted to biological data from 165 springs to identify bryophyte and invertebrate surrogates for taxonomic and functional diversity of boreal springs. We focused on these 2 groups because they are well known and abundant in most boreal springs. The best indicators of taxonomic versus functional diversity differed. The bryophyte Bryum weigelii and the chironomid larva Paratrichocladius skirwithensis best indicated taxonomic diversity, whereas the isopod Asellus aquaticus and the chironomid Macropelopia spp. were the best surrogates of functional diversity. In a scoring algorithm for priority‐site selection, taxonomic surrogates performed only slightly better than random selection for all spring‐dwelling taxa, but they were very effective in representing spring specialists, providing a distinct improvement over random solutions. However, the surrogates for taxonomic diversity represented functional diversity poorly and vice versa. When combined with cross‐taxon complementarity analyses, surrogate selection based on statistical modeling provides a promising approach for identifying groundwater‐dependent ecosystems of special conservation value, a key requirement of the EU Water Framework Directive.

Thermal and hydrologic responses to climate change predict marked alterations in boreal stream invertebrate assemblages - Kaisa‐Riikka Mustonen; Heikki Mykrä; Hannu Marttila; Romain Sarremejane; Noora Veijalainen; Kalle Sippel; Timo Muotka; Charles P. Hawkins (Global Change Biology, 2018)
Air temperature at the northernmost latitudes is predicted to increase steeply and precipitation to become more variable by the end of the 21st century, resulting in altered thermal and hydrological regimes. We applied five climate scenarios to predict the future (2070–2100) benthic macroinvertebrate assemblages at 239 near‐pristine sites across Finland (ca. 1200 km latitudinal span). We used a multitaxon distribution model with air temperature and modeled daily flow as predictors. As expected, projected air temperature increased the most in northernmost Finland. Predicted taxonomic richness also increased the most in northern Finland, congruent with the predicted northwards shift of many species’ distributions. Compositional changes were predicted to be high even without changes in richness, suggesting that species replacement may be the main mechanism causing climate‐induced changes in macroinvertebrate assemblages. Northern streams were predicted to lose much of the seasonality of their flow regimes, causing potentially marked changes in stream benthic assemblages. Sites with the highest loss of seasonality were predicted to support future assemblages that deviate most in compositional similarity from the present‐day assemblages. Macroinvertebrate assemblages were also predicted to change more in headwaters than in larger streams, as headwaters were particularly sensitive to changes in flow patterns. Our results emphasize the importance of focusing protection and mitigation on headwater streams with high‐flow seasonality because of their vulnerability to climate change.

Do metacommunities vary through time? Intermittent rivers as model systems - Romain Sarremejane; Miguel Cañedo‐Argüelles; Narcís Prat; Heikki Mykrä; Timo Muotka; Núria Bonada (Journal of Biogeography, 2017)
Aim Metacommunity assembly mechanisms have been traditionally considered stable through time. However, in highly dynamic systems with varying local environmental conditions and patch connectivity, communities are likely to experience temporal shifts in their assembly mechanisms. Here, we used a set of perennial ( PR ) and intermittent ( IR ) rivers to assess if assembly mechanisms vary seasonally in response to flow intermittence. Location Mediterranean climate region (100,000 km 2 ), Spain. Methods We used a modelling approach to assess the relative effect of environmental sorting and dispersal‐based processes on aquatic invertebrate metacommunities within and across river types at four distinct hydrological periods. We used local environmental variables to assess environmental sorting, and considered geographical, network and topographical distances as different dispersal surrogates. Linear mixed effect models accounting for the non‐independence of pairwise distances were used to assess the relationships between community dissimilarity and distance matrices. Results Assembly mechanisms were more temporally stable in PR than in IR . In PR , community dissimilarities were equally related to environmental and geographical distances suggesting codominance of species sorting and dispersal‐based assembly mechanisms. In IR , environmental distance best explained community dissimilarities during the dry period when flow cessation imposes strong environmental sorting, whereas metacommunity organization was much more stochastic during the rewetting period when high flows may randomly reorganize communities. Dispersal processes dominated assembly mechanisms between PR and IR during the rewetting period suggesting an increase in recolonization processes linking both river types following the dry period. Geographical and topographical distances best explained community variability, suggesting that overland dispersal dominates in river networks fragmented by drying events. Main conclusions Aquatic invertebrate metacommunity assembly mechanisms vary seasonally in response to changes in hydrological conditions. The temporal dimension should be better incorporated into metacommunity studies in highly dynamic systems such as intermittent rivers.

Does habitat restoration enhance spring biodiversity and ecosystem functions? - Kaisa Lehosmaa; Jussi Jyväsjärvi; Risto Virtanen; Pekka M. Rossi; Dimitrios Rados; Tatiana Chuzhekova; Annamari Markkola; Jari Ilmonen; Timo Muotka (Hydrobiologia, 2017)

Climate‐induced warming imposes a threat to north European spring ecosystems - Jussi Jyväsjärvi; Hannu Marttila; Pekka M. Rossi; Pertti Ala‐Aho; Bo Olofsson; Jakob Nisell; Birgitta Backman; Jari Ilmonen; Risto Virtanen; Lauri Paasivirta; Ritva Britschgi; Bjørn Kløve; et al. (Global Change Biology, 2015)
Interest in climate change effects on groundwater has increased dramatically during the last decade. The mechanisms of climate‐related groundwater depletion have been thoroughly reviewed, but the influence of global warming on groundwater‐dependent ecosystems (GDEs) remains poorly known. Here we report long‐term water temperature trends in 66 northern European cold‐water springs. A vast majority of the springs (82%) exhibited a significant increase in water temperature during 1968–2012. Mean spring water temperatures were closely related to regional air temperature and global radiative forcing of the corresponding year. Based on three alternative climate scenarios representing low (RCP2.6), intermediate (RCP6) and high‐emission scenarios (RCP8.5), we estimate that increase in mean spring water temperature in the region is likely to range from 0.67 °C (RCP2.6) to 5.94 °C (RCP8.5) by 2086. According to the worst‐case scenario, water temperature of these originally cold‐water ecosystems (regional mean in the late 1970s: 4.7 °C) may exceed 12 °C by the end of this century. We used bryophyte and macroinvertebrate species data from Finnish springs and spring‐fed streams to assess ecological impacts of the predicted warming. An increase in spring water temperature by several degrees will likely have substantial biodiversity impacts, causing regional extinction of native, cold‐stenothermal spring specialists, whereas species diversity of headwater generalists is likely to increase. Even a slight (by 1 °C) increase in water temperature may eliminate endemic spring species, thus altering bryophyte and macroinvertebrate assemblages of spring‐fed streams. Climate change‐induced warming of northern regions may thus alter species composition of the spring biota and cause regional homogenization of biodiversity in headwater ecosystems.

Distance decay of similarity in freshwater communities: do macro‐ and microorganisms follow the same rules? - Anna Astorga; Jari Oksanen; Miska Luoto; Janne Soininen; Risto Virtanen; Timo Muotka (Global Ecology and Biogeography, 2012)
Aim An intensively debated issue in macroecology is whether unicellular organisms show biogeographic patterns different from those of macroorganisms. One aspect of this debate addresses beta diversity, that is, do microbial organisms exhibit distance‐decay patterns similar to those of macroorganisms? And if so, is the decay of community similarity caused by spatially limited dispersal or by niche‐related factors? We studied the community similarity of stream diatoms, macroinvertebrates and bryophytes across the same set of sites in relation to environmental and geographic distance. Location A geographical gradient of c . 1100 km in Finland. Methods We first identified the subset of environmental variables that produced the highest correlation with community similarities for each taxonomic group. Based on these variables, we used partial Mantel tests to separate the independent influences of environmental and geographical distance for distance decay of community similarity, separately for diatoms, bryophytes and macroinvertebrates. Finally, macroinvertebrates were divided into three groups based on their different dispersal categories and a partial Mantel test was used to assess whether each of these groups were differently affected by environmental versus geographic distance, i.e. is dispersal a key factor in tests of niche versus neutral models. Results The level of environmental control was by far the strongest for diatoms; however, all groups were controlled more by environmental factors than by limited dispersal. Macroinvertebrate species with low dispersal ability were significantly related to geographic distance, while more effective dispersers showed no relationship to geography but were instead strongly related to environmental distance. Main conclusions Our results suggest that patterns between macro‐ and microorganisms are not fundamentally different, but the level of environmental control varies according to dispersal ability. The relative importance of niche versus dispersal processes is not simply a function of organism size but other traits (e.g. life‐history type, dispersal capacity) may obscure this relationship.

Invasion of north European streams by brook trout: hostile takeover or pre-adapted habitat niche segregation? - Kai Korsu; Ari Huusko; Timo Muotka (Biological Invasions, 2010)

Regional and local drivers of macroinvertebrate assemblages in boreal springs - Jari Ilmonen; Lauri Paasivirta; Risto Virtanen; Timo Muotka (Journal of Biogeography, 2009)
Aim To identify the most important environmental drivers of benthic macroinvertebrate assemblages in boreal springs at different spatial scales, and to assess how well benthic assemblages correspond to terrestrially derived ecoregions. Location Finland. Methods Benthic invertebrates were sampled from 153 springs across four boreal ecoregions of Finland, and these data were used to analyse patterns in assemblage variation in relation to environmental factors. Species data were classified using hierarchical divisive clustering ( twinspan ) and ordinated using non‐metric multidimensional scaling. The prediction success of the species and environmental data into a priori (ecoregions) and a posteriori ( twinspan ) groups was compared using discriminant function analysis. Indicator species analysis was used to identify indicator taxa for both a priori and a posteriori assemblage types. Results The main patterns in assemblage clusters were related to large‐scale geographical variation in temperature. A secondary gradient in species data reflected variation in local habitat structure, particularly abundance of minerogenic spring brooks. Water chemistry variables were only weakly related to assemblage variation. Several indicator species representing southern faunistic elements in boreal springs were identified. Discriminant function analysis showed poorer success in classifying sites into ecoregions based on environmental than on species data. Similarly, when classifying springs into the twinspan groups, classification based on species data vastly outperformed that based on environmental data. Main conclusions A latitudinal zonation pattern of spring assemblages driven by regional thermal conditions is documented, closely paralleling corresponding latitudinal patterns in both terrestrial and freshwater assemblages in Fennoscandia. The importance of local‐scale environmental variables increased with decreasing spatial extent. Ecoregions provide an initial stratification scheme for the bioassessment of benthic macroinvertebrates of North European springs. Our results imply that climate warming, landscape disturbance and degradation of spring habitat pose serious threats to spring biodiversity in northern Europe, especially to its already threatened southern faunistic elements.

Local–regional diversity relationship varies with spatial scale in lotic diatoms - Janne Soininen; Jani Heino; Mikolaj Kokocinski; Timo Muotka (Journal of Biogeography, 2009)
Aim Ecologists have shown increasing interest in the relative roles of local and regional factors in structuring biotic communities. One approach to studying this is to examine the relationship between local species richness (LSR) and regional species richness (RSR). We examined the LSR–RSR relationship in stream diatoms, using two data sets that varied in spatial extent. At broad spatial extent ranging across drainage systems, we expected climatic and dispersal‐related factors to constrain LSR, thus resulting in a linear LSR–RSR relationship. However, at small spatial scales dispersal across sites should be unconstrained, resulting in strong local interactions and a weak or asymptotic LSR–RSR relationship. Location Boreal streams in Finland. Methods For data set 1, we sampled 15 stream riffles (localities) in each of eight drainage systems (regions), with the latitudinal gradient between the southernmost and northernmost sites being almost 1100 km. For data set 2, a locality for estimating LSR was a single stone, and each riffle represented a region for estimating RSR. We sampled 20 stones in each of eight riffles. We used linear regressions to examine the relationship between LSR and RSR across regions. We used both observed richness values, as well as values estimated with the Chao1 estimator. Results We found a relatively strong linear relationship between the Chao1‐estimated mean LSR and RSR ( R 2 = 0.654, P = 0.015) across drainage systems. The slope of the regression was 0.643 and it did not differ from 1.0, thus indicating linearity. At the riffle scale, however, LSR and RSR were not linearly related, and the slope of the regression (0.039) differed significantly from 1.0, indicating curvilinearity. Main conclusions These results suggest that the relationship between mean LSR and RSR varies across spatial scales in diatoms – from significantly linear at large scales to curvilinear at small scales. These plots imply strong regional enrichment in stream diatoms across drainage systems. Their diversity is thus determined largely by the composition of the regional species pool, as also in many macroorganisms. In contrast, at small spatial scales the LSR–RSR relationship implied a hard limit to local diversity, reflecting the primacy of local processes.

Does the introduced brook trout (Salvelinus fontinalis) affect growth of the native brown trout (Salmo trutta)? - Kai Korsu; Ari Huusko; Timo Muotka (The Science of Nature, 2009)

Diatoms: unicellular surrogates for macroalgal community structure in streams? - Janne Soininen; Riku Paavola; Janina Kwandrans; Timo Muotka (Biodiversity and Conservation, 2009)

Scale‐related patterns in the spatial and environmental components of stream macroinvertebrate assemblage variation - Heikki Mykrä; Jani Heino; Timo Muotka (Global Ecology and Biogeography, 2007)
Aim We examined the relative contributions of spatial gradients and local environmental conditions to macroinvertebrate assemblages of boreal headwater streams at three hierarchical extents: bioregion, ecoregion and drainage system. We also aimed to identify the environmental variables most strongly related to assemblage structure at each study scale, and to assess how the importance of these variables is related to regional context and spatial structuring at different scales. Location Northern Finland ( 62 – 68° N, 25–32° E). Methods Variation in macroinvertebrate data was partitioned using partial canonical correspondence analysis into components explained by spatial variables (nine terms from the cubic trend surface regression), local environmental variables (15 variables) and spatially structured environmental variation. Results The strength of the relationship between assemblage structure and local environmental variables increased with decreasing spatial extent, whereas assemblage variation related to spatial variables and spatially structured environmental variation showed the opposite pattern. At the largest extents, spatial variation was related to latitudinal gradients, whereas spatial autocorrelation among neighbouring streams was the likely mechanism creating spatial structure within drainage systems. Only stream size and water acidity were consistently important in explaining assemblage structure at all study scales, while the importance of other environmental variables was more context‐dependent. Main conclusions The importance of local environmental factors in explaining macroinvertebrate assemblage structure increases with decreasing spatial extent. This scale‐related pattern is not caused solely by changes in study extent, however, but also by variable sample sizes at different regional extents. The importance of environmental gradients is context‐dependent and few factors are likely to be universally important correlates of macroinvertebrate assemblage structure. Finally, our results suggest that bioassessment should give due attention to spatial structuring of stream assemblages, because important assemblage gradients may not only be related to local factors but also to biogeographical constraints and neighbourhood dispersal processes.

Scale-related patterns in the spatial and environmental components of stream macroinvertebrate assemblage variation - Heikki Mykrä; Jani Heino; Timo Muotka (Global Ecology and Biogeography, 2006)

Characterizing macroinvertebrate assemblage structure in relation to stream size and tributary position - Jani Heino; Juha Parviainen; Riku Paavola; Michael Jehle; Pauliina Louhi; Timo Muotka (Hydrobiologia, 2005)

Searching for biodiversity indicators in running waters: do bryophytes, macroinvertebrates, and fish show congruent diversity patterns? - Jani Heino; Riku Paavola; Risto Virtanen; Timo Muotka (Biodiversity and Conservation, 2005)

Variability of Lotic Macroinvertebrate Assemblages and Stream Habitat Characteristics Across Hierarchical Landscape Classifications - Heikki Mykr; Jani Heino; Timo Muotka (Environmental Management, 2004)

Fecal pellets from a dense aggregation of suspension‐feeders in a stream: An example of ecosystem engineering - Roger S. Wotton; Björn Malmqvist; Timo Muotka; Kristina Larsson (Limnology and Oceanography, 1998)
Blackfly larvae (Diptera: Simuliidae) are “allogenie ecosystem engineers” that capture fine particulate and dissolved matter from suspension and egest much larger fecal pellets. We investigated the effects of blackfly larvae on organic matter transport at 25 sites along a small stream that flowed 500 m from a lake to the sea. Blackfly density was high upstream (>6 × 10 5 ind. m −2 ) and the numbers of fecal pellets in suspension rose markedly downstream from the blackfly aggregation. A total of 1.6 × 10 9 fecal pellets (biomass 3.2 kg C d −1 ) were discharged to the sea each day and 8.0 × 10 8 pellets (biomass 1.6 kg C d −1 ) were lost from suspension. Sedimenting pellets were available to the benthic microbial and invertebrate communities.